Sadfishing or emotional baiting: The pursuit of interaction and followers through emotional posts on social media - Com, Senol; Unlu, Zeki Can; Aytas, Murat (Edelweiss Applied Science and Technology, 2025)
This study examines the phenomenon of “sadfishing,” defined as the exaggerated sharing of emotional content on social media to attract attention. Sadfishing involves users amplifying feelings of sadness or stress to garner empathy or support from online communities. As this phenomenon grows, it has become a popular strategy among both young people and adults as they shape their online identities. The study explores the impacts of sadfishing on social media users, its psychological consequences, and the potential long-term effects on social relationships. While sadfishing evokes empathy, it also raises questions about authenticity and invites humorous criticism. In this context, the study aims to investigate the potential risks associated with emotional manipulation and exaggerated sharing on social media and their impact on digital interaction dynamics. The research analyzes sadfishing-related posts from the TikTok user @burcemiyyy using a qualitative research method, specifically netnographic analysis. This analysis evaluates user comments under four main themes: Empathy and Supportive Comments, Questioning Sincerity, Humorous and Satirical Reactions, and Advice and Guidance Comments. The findings reveal that social media users respond to sadfishing content in various ways, and these posts can trigger diverse social and psychological dynamics. These results suggest that sadfishing content generates effects not only on an individual level but also on a societal level, providing a new perspective within the context of social media ethics and digital citizenship.